Aphthous lesions turned out to be neonatal very early-onset inflammatory bowel disease: a case report - Hutmacher, Felix; Doerig, Selina; Grobholz, Rainer; Köhler, Henrik; Meyer, Philipp; Baumann, Philipp (Frontiers in Pediatrics, 2024)
Globally, inflammatory bowel disease (IBD) incidence rises. Neonatal diagnosis of inflammatory bowel disease (IBD) proves challenging due to its nonspecific symptoms. A term-born neonate showing states of inflammation and aphthae was treated for sepsis and candidiasis before being diagnosed with interleukin-10-receptor deficiency and consecutive IBD. The patientthat was finally successfully treated by stem cell transplantation. The case illustrates the difficulties of the diagnostic course in IBD as it may mimic other diseases and emphasizes the importance of considering rare differential diagnoses early in the diagnostic process. This emphasizes considering IBD when standard thrush treatment fails.